THE INFLUENCE OF COMPENSATION AND WORK MOTIVATION ON JOB SATISFACTION AT PT.MMP CENTRAL SULAWESI - Widodo, Diky Arif; Swasti, Ika Korika (International Journal of Multidisciplinary Research and Literature, 2024)
An organization or institution is established with specific goals, and the achievement of these objectives is influenced by the behavior and attitudes of its human resources. The success of an organization depends on the contributions of its human resources. The purpose of this study is to determine whether compensation and work motivation have an impact on job satisfaction at PT. Morowali Mitra Perkasa. A quantitative research method is applied in this study, with job satisfaction as the dependent variable and compensation and work motivation as independent variables. The total population of this study is 602 employees. The research sample is determined using Probability Sampling, applying the Simple Random Sampling method, using calculations with the Slovin formula. It is known that the sample size considered representative of the population is 86 respondents. The research analysis method uses Partial Least Squares (PLS). The results of this study can be summarized as follows: 1) Compensation plays a role in job satisfaction. 2) Work motivation plays a role in job satisfaction